607 Impact of anifrolumab on neuropsychiatric manifestations of depression and suicidality in patients with systemic lupus erythematosus. (14th December 2022) - Manzi, Susan; Lindholm, Catharina; Hupka, Ihor; ,; Shroff, Manish; Abreu, Gabriel; Werther, Shanti; Tummala, Raj
Abstract : Background: Neuropsychiatric (NP) disease is more common in patients with systemic lupus erythematosus (SLE) than in the general population. 1 Increased incidence of NP events (depression and suicidality) has been reported with biologic therapies, including SLE therapies. 2 Depression and suicidality were evaluated in patients with SLE treated with anifrolumab, a type I interferon receptor antibody, in the TULIP-1 and TULIP-2 trials. 3, 4 This analysis aims to understand the impact of anifrolumab treatment on NP manifestations (depression and suicidality) in patients with SLE relative to standard therapy using pooled data from the TULIP trials. Methods: TULIP-1/-2 were randomized, placebo-controlled, 52-week trials of intravenous anifrolumab every 4 weeks in patients with moderate to severe SLE despite standard therapy. 3, 4 Patients with active severe or unstable NP SLE were excluded. Patients who received ≥1 dose of anifrolumab 300 mg or placebo were analyzed for depression and suicidality . 3, 4 The Personal Health Questionnaire Depression Scale-8 (PHQ-8) and Columbia Suicide Severity Rating Scale (C-SSRS) were used to assess clinical depression and suicidal ideation and behavior, respectively. Incidence of adverse events (AEs) within the standardized Medical Dictionary for Regulatory Activities query of depression (excluding suicide and self-injury) and antidepressant use at baseline and during the study were also assessed. Results: In the TULIP pooled analysis, 360 patients received anifrolumab and 365 received placebo. Mean PHQ-8 scores were in the mild range (≥5 to <10); 9.7 in both groups at baseline (table 1). Excluding patients taking antidepressants, mean PHQ-8 scores were 9.5 in the anifrolumab group and 9.7 in the placebo group at baseline. No clinically meaningful worsening in mean PHQ-8 scores was observed from baseline to Week 52 in the anifrolumab (–2.0) or placebo (–1.3) groups; excluding patients taking antidepressants, mean changes in PHQ-8 were –2.0 and –1.2, respectively. Depression AEs during the study were reported in 11 anifrolumab-treated patients (3.1%) and 9 patients who received placebo (2.5%). At baseline, antidepressant use was comparable between groups (anifrolumab group, 7 patients [1.9%]; placebo group, 9 patients [2.5%]). During the study, 8 anifrolumab-treated patients (2.2%) and 12 patients who received placebo (3.3%) used antidepressants; 1 (0.3%) and 4 (1.1%) patients, respectively, initiated antidepressant therapy during the study (1 in the placebo group stopped therapy). Suicidal ideation or behavior, as assessed by C-SSRS, during the study was reported in 5 anifrolumab- treated patients (1.4%) and 11 patients who received placebo (3.0%). Excluding patients taking antidepressants, suicidal ideation or behavior during the study was reported in 4 anifrolumab-treated patients (1.1%) and 9 patients who received placebo (2.5%) (figure 1). Conclusions: Patients with SLE treated with anifrolumab did not experience increased depression, suicidality, or need for antidepressants when compared with standard therapy, irrespective of baseline antidepressant use. References: Zhang L, et al . BMC Psychiatry . 2017;17 :70. Benlysta (belimumab) [prescribing information]. Philadelphia, PA: GlaxoSmithKline; 2021. Furie RA, et al . Lancet Rheumatol . 2019;1 :e208–19. Morand EF, et al . N Engl J Med. 2020;382 :211–21. Acknowledgements: Writing assistance by Andrea Y. Angstadt, PhD (Fishawack Health). This study was sponsored by AstraZeneca. Submission deadline: August 1, 2022 at 11:59 PM EST Disclosures: SM has received speaker fees from AstraZeneca; received consulting fees from AstraZeneca, Exagen Diagnostics, Inc, Cugene, GSK, Lilly, Lupus Foundation of America, and UCB Advisory Board; received grant support from HGS/GSK, AstraZeneca, and AbbVie. CL, IH, MS, and GA are employees of AstraZeneca. LZ, SW and RT are employees and shareholders of AstraZeneca.